Undrained Dynamic Behavior of Reinforced Subgrade under Long-Term Cyclic Loading - Min Geng; Debin Wang; Peiyong Li (Advances in Materials Science and Engineering)
To study the dynamic behavior of reinforced subgrade, a series of undrained cyclic triaxial tests of reinforced soil (the specimen a height of 50 cm and a diameter of 20 cm) were performed in this paper. The specimens were tested by varying confining pressure, vibration frequency, dynamic stress amplitudes, and reinforced layers. Orthogonal experiment is a better way to optimize the process of experiment. Impact on dynamic behavior of the reinforced soil specimens is discussed through orthogonal design of experiments in four factors and three levels. This study has demonstrated that the order of dynamic elastic modulus of reinforced soil is influenced by dynamic stress amplitude, frequency, reinforced layer, and confining pressure within changing in factor level. The dynamic stress amplitude has great influence on the dynamic elastic modulus of reinforced soil. The bearing capacity and dynamic elastic modulus of reinforced subgrade decrease slightly with the increase of dynamic strain. Frequency has an influence on the dynamic elastic modulus. It is shown that the cumulative strain of reinforced soil is related to the vibration frequency. The test results also exemplify the reinforced subgrade restrict lateral displacement of subgrade and reduce settlement of subgrade under long-term cyclic loading.